Posttranslational Modification of Flagellin FlaB in Shewanella oneidensis - Sun, Linlin (American Society for Microbiology, 2013)
Shewanella oneidensis is a highly motile organism by virtue of a polar, glycosylated flagellum composed of flagellins FlaA and FlaB. In this study, the functional flagellin FlaB was isolated and analyzed with nano-liquid chromatography-mass spectrometry (MS) and tandem MS. In combination with the mutational analysis, we propose that the FlaB flagellin protein from S. oneidensis is modified at five serine residues with a series of novel O-linked posttranslational modifications (PTMs) that differ from each other by 14 Da. These PTMs are composed in part of a 274-Da sugar residue that bears a resemblance to the nonulosonic acids. The remainder appears to be composed of a second residue whose mass varies by 14 Da depending on the PTM. Further investigation revealed that synthesis of the glycans initiates with PseB and PseC, the first two enzymes of the Pse pathway. In addition, a number of lysine residues are found to be methylated by SO4160, an analogue of the lysine methyltransferase of Salmonella enterica serovar Typhimurium.